Reinstatement in Civil Employment - TUC leaflet, 1944 (pg. 3) (1944)
1944 1939-1945 "Reinstatement in Civil Employment - TUC leaflet, 1944 (pg. 3)" [HFR0068c], 1944 This TUC guide to the Reinstatement in Civil Employment Act 1944 explains the re-employment rights of members of the armed forces, women's services and civil defence workers after demobilisation and the end of the war.